Self Healing dalam Al-Qur’an: (Dirâsah Tafsir Tahlili Surat Ad-Duha) - Asif Trisnani; Alda Rizmardini; Nurul Aspi (Qolamuna : Jurnal Studi Islam, 2026)
The era of rapid advances in technology and information has had a major impact, one of which is mental health disorders. Recently, mental health issues have been increasingly voiced due to changes in lifestyle, social environment, and technology that require humans to adjust to the various demands of modern life. These problems include many people who experience psychological disorders due to criticism, responses, and bad judgment from others. However, all forms of anxiety can be overcome with self-healing. The purpose of this study is to explore the self-healing method as a self-healing from the disease in the chest and analyze the relevance of the content of Surah Ad-Duha to self-healing. The research method used is a qualitative study method in the form of library research, using an analytical method approach (tahlili) in interpreting the content of self-healing verses in Surah Ad-Duha. The results show that Surah Ad-Duha offers a Qur'anic self-healing model centered on three main mechanisms, namely (1) restoration of divine affection through strengthening the sense of being cared for and not abandoned; (2) reconstruction of the meaning of life through remembrance of blessings, strengthening self-identity, and affirmation that difficulties are always accompanied by ease; and (3) activation of the ethic of devotion through encouragement to give, do good, and live life with spiritual optimism. Thus, Surah Ad-Duha not only provides theological reinforcement, but also offers an integrative self-healing framework that is relevant to contemporary mental health problems. Keywords: Self-healing, Tafsir Tahlili, surat Ad-Duha, Psychospiritual